Normative scales for assessing static equilibrium in junior schoolchildren - Skotnikova A.V.; Aleksandrova V.A.; Serikova Yu.N.; Ovchinnikov V.I. (Theory and Practice of Physical Culture, 2024)
Objective of the study was to develop normative scales for assessing static balance in younger schoolchildren. Methods and structure of the study. The scientific work was carried out on the basis of school 1476 in Moscow, in which 570 elementary school students took part. A comprehensive assessment of the physical development of children of primary school age was carried out. For static balance of junior schoolchildren, a complicated non-instrumental Romberg test was used. The use of the Romberg test is based on the assessment of vertical stability and stability of a person’s posture, which involves identifying the degree of contribution of different sensory systems. Maintaining a stable posture is ensured by: vision, vestibular apparatus, proprioception. In the Romberg test, performed in a calm state on a stationary support, provided there are no disorders of the vestibular apparatus, the activity of the visual system and proprioception is assessed to a greater extent. In the practice of physical education and sports, the Romberg test is also quite often used for comprehensive testing of schoolchildren. Results and conclusions. Centile scales have been developed to evaluate the Romberg test on one leg with open and closed eyes; visual control has a significant impact on primary school students when performing a test exercise for static balance. The experiment revealed the dominance of the right leg relative to the left.